Distribution of ixodid ticks of cattle and associated risk factors in and around Guder town, west Shewa zone, Oromia, Ethiopia - Isayas Asefa Kebede; Kirubel Abreham; Asemamaw Alemayew; Dimamnesh Worku; Tefera Tarekagne; Megersa Akasa Debele; Segni Bedasa Gudina; Abrahim Dawed Ahmed; Haben Fesseha Gebremeskel (Parasite Epidemiology and Control)
Ticks are the most prominent ectoparasites of cattle, causing significant losses. From March to May 2024, a cross-sectional study was carried out in and around Guder town of the west Shewa zone of the Oromia region, Ethiopia, to identify species of ixodid ticks infesting cattle and estimate their prevalence and associated risk factors. Adult ixodid ticks were collected from 200 cattle using systematic random sampling methods and classified into species based on their morphology using a stereomicroscope. Of the examined cattle, 75.0 % (95 % CI: 68.5–80.6) were infested with one or more tick species. The highest prevalence of tick parasites was recorded in Mamo Mezemir kebele, male, young, extensive management system, and good-body condition of cattle, with prevalences of 94.7 %, 87.5 %, 86.7 %, 77.6 %, and 80.0 %, respectively compared to counterparts. Four genera of ticks were identified viz. Amblyomma, Rhipicephalus (Boophilus), Hyalomma, and Rhipicephalus. A total of 702 ticks were collected. Rhipicephalus evertsi evertsi and Hyalomma rufipes were the most (38.7 %) and least (8.1 %) abundant tick species, respectively. The peasant associations and sex were the only risk factors associated with the tick infestations (p < 0.05). Cattle in the Mamo Mezemir kebele were 17 (OR = 16.9; 95 %CI: 1.9–149.2) times more likely to be infested by ticks than those in other regions. This study shows that ticks were a most significant concern for cattle in the studied area. Thus, strategic tick control, which includes the use of acaricides, and creating awareness for the livestock owners about the impact of tick infestation is recommended.